Barbados. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
IICA organized its annual Youth Farm Program, providing training in crop, livestock, and aquaponics production to 30 participants from Barbados and 8 from Antigua and Barbuda. The institute also facilitated the participation of 38 individuals from Antigua and Barbuda in the program, contributing to increasing the number of youth equipped to enhance food and nutritional security. IICA also promoted an urban and mobile backyard aquaponics unit, established an online community of backyard producers, and developed a program to boost trade and marketing by micro, small, and medium-sized agri-entrepreneurs. The Institute also led efforts to provide training in backyard gardening and procured equipment and machinery to establish the Barbados Innovation Center for Agriculture. The institute coordinated the execution of the Caribbean Virtual Agri-Food Trade Mission and continued to coordinate the execution of the 11th EDF SPS Measures Project to assist the region in modernizing agricultural health and food safety systems.